THE COMPARATIVE STUDY OF P-CHART USING SIMPLE RANDOM SAMPLES AND MAXIMA NOMINATED SAMPLES - AFRIANI (NIM : 10109076); pembimbing : Dr. Udjianna S. Pasaribu ; Dr. Utriweni Mukhaiyar, NIZLA
Control chart for attribute is based on qualitative data. One of type attributes control charts for monitoring the nonconforming or conforming items in a population is P-chart. Two methods of P-chart development regarding the method of sampling are Simple Random Samples (SRS) and Maxima Nominated Samples (MNS). Hence, the research showed the comparison of P-chart between SRS and MNS method based on the formula of construction, behavior and determination of minimum sample size. The result of this paper are P-chart with MNS method has a tighter chart than SRS method, especially for a greater sample size and number of batches. In other words, MNS has a smaller minimum sample size than SRS in sampling